The primary benefits of screencasting for Maths learning: Findings of an Irish case study - Tunku Ahmad, Tunku Badariah; Doheny, Frank (2013)
This qualitative case study explored the views of Irish college students regarding the benefits of screencasts in enhancing their Maths learning experience. A total of 47 Maths screencasts were uploaded onto the relevant Maths Moodle pages for students to access. An open-response survey asking about the benefits of the screencasts and how they helped students to learn the course content was administered online. Out of the 266 first, second and third year students taking the Maths courses in Algebra and Calculus, 138 responded to the survey (52% response rate). The data were analysed using an inductive thematic content analysis. Themes that represented different types of screencast use and benefits were generated from the clustering of feedback. The findings pointed to six primary benefits of screencasts, which included supporting flexible and personalized learning, supplementing lectures and enhancing understanding of Maths keyskills, delivering a vicarious learning experience, facilitating exam revision and material review, providing multimodal support for Maths learning, and helping students to keep track with Maths modules. The findings have positive impli-cations for screencasts as a promising tool for Maths learning in future decades